2019
DOI: 10.1101/734012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol recognition motifs in the transmembrane domain of the tyrosine kinase receptor family: the case for TRKB

Abstract: Cholesterol is an essential constituent of cell membranes. Recently, the discovery of cholesterol recognition amino acid consensus (CRAC) on proteins indicated a putative direct, non-covalent interaction between cholesterol and proteins. In the present study, we evaluated the presence of a CRAC motif and its inverted version (CARC) in the transmembrane region (TMR) of the tyrosine kinase receptor family (RTK) in several species using in silico methods. CRAC motifs were found across all species analyzed, while … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…For the experiments assessing the effect of PTPσ genetic deficiency on pTRKB in vitro, cortical cell cultures were prepared from balb/c mouse embryos (PTPσ -/-, PTPσ +/and their WT littermates) extracted on embryonic day 18 (E18) using the same protocol as described above for the plasmid purchased from OriGene (#RR209636), pCMV6-Entry vector with C-terminal Myc-DDK Tag (#PS100001) was used to transfect control cells. HEK293T were transfected with GFP-tagged fulllength TRKB plasmid (HP220GFP-TRKB) (Haapasalo et al, 2001) or TRKB carrying Y433F/R427A mutation (Cannarozzo et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the experiments assessing the effect of PTPσ genetic deficiency on pTRKB in vitro, cortical cell cultures were prepared from balb/c mouse embryos (PTPσ -/-, PTPσ +/and their WT littermates) extracted on embryonic day 18 (E18) using the same protocol as described above for the plasmid purchased from OriGene (#RR209636), pCMV6-Entry vector with C-terminal Myc-DDK Tag (#PS100001) was used to transfect control cells. HEK293T were transfected with GFP-tagged fulllength TRKB plasmid (HP220GFP-TRKB) (Haapasalo et al, 2001) or TRKB carrying Y433F/R427A mutation (Cannarozzo et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…MG87.TRKA and MG87.TRKB cells were transfected with PTPσ (RefSeq number NM_019140) Myc-DDK-tagged open-reading frame (ORF) plasmid purchased from OriGene (#RR209636), pCMV6-Entry vector with C-terminal Myc-DDK Tag (#PS100001) was used to transfect control cells. HEK293T were transfected with GFP-tagged full-length TRKB plasmid (HP220GFP-TRKB; Haapasalo et al, 2001 ) or TRKB carrying Y433F/R427A mutation ( Cannarozzo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MG87.TRKA and MG87.TRKB cells were transfected with PTPσ (RefSeq number NM_019140) Myc-DDK-tagged open-reading frame (ORF) plasmid purchased from OriGene (#RR209636), pCMV6-Entry vector with C-terminal Myc-DDK Tag (#PS100001) was used to transfect control cells. HEK293T were transfected with GFP-tagged full-length TRKB plasmid (HP220GFP-TRKB)(Haapasalo et al, 2001) or TRKB carrying Y433F/R427A mutation (Cannarozzo et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of regulation of BDNF-dependent processes may be associated with the ability of Sigma1R to bind and transport cholesterol during ligand activation due to the presence of cholesterol recognition or interaction of amino acid consensus sequences (CRAC/CARC) [ 66 , 73 , 167 ]. Pilot studies have shown that CRAC/CARC motifs are present in the trkB sequence [ 168 ], and cholesterol itself is able to stimulate trkB phosphorylation [ 169 ]. The activity of both Sigma1R and trkB is associated with their localization in cholesterol-rich lipid domains [ 73 , 170 , 171 , 172 , 173 ], while Sigma1R ligands fluoxetine and escitalopram have the ability to accumulate in lipid rafts [ 174 ].…”
Section: Contribution Of Sigma1r Chaperone To the Molecular Mechanmentioning
confidence: 99%